Satire, Veneration, and St. Joseph in Art, c. 1300-1550 - Williams, Anne L. (Book collections on Project MUSE., 2019)
Satire, Veneration, and St. Joseph in Art, c. 1300-1550 is the first to reclaim satire as a central component of Catholic altarpieces, devotional art, and veneration, moving beyond humor's relegation to the medieval margins or to the profane arts alone. The book challenges humor's perception as a mere teaching tool for the laity and the antithesis of 'high' veneration and theology, a divide perpetuated by Counter-Reformation thought and the inheritance of Mikhail Bakhtin (Rabelais and His World, 1965). It reveals how humor, laughter, and material culture played a critical role in establishing St. Joseph as an exemplar in western Europe as early as the thirteenth century. Its goal is to open a new line of interpretation in medieval and early modern cultural studies, by revealing the functions of humor in sacred scenes, the role of laughter as veneration, and the importance of play for pre-Reformation religious experiences.